Tanshinone IIA Protects Hippocampal Neuronal Cells from Reactive Oxygen Species Through Changes in Autophagy and Activation of Phosphatidylinositol 3-Kinase, Protein Kinas B, and Mechanistic Target of Rapamycin Pathways - Zhu, Yingchun (Curr Neurovasc Res, 2017)
BACKGROUND: Tanshinone IIA is a key active ingredient of danshen, which is derived from the dried root or rhizome of Salviae miltiorrhizae Bge. The tanshinone IIA has protective effects against the focal cerebral ischemic injury. However, the underlying mechanisms remain unclear. METHODS: An in vitro model of cerebral ischemia was established by subjecting cultures of hippocampal neuronal cells to oxygen-glucose deprivation followed by reperfusion (OGD/R). The probes of 5-(and-6)-chloromethyl-2’,7’-dichlorodihydrofluorescein diacetate, acetyl ester (CM-H2DCFDA) and 5’,6,6’-tetrachloro-1,1’,3,3’-tetraethylbenzimidazolylcarbocyanine,iodide (JC-1) were used to determine the mitochondrial membrane potential (MMP) and reactive oxygen species (ROS) production. Western-blot was used to detect the expression of proteins in HT-22 cells. RESULTS: The results of cell proliferative assays showed that the tanshinone IIA attenuated OGD/R-mediated neuronal cell death, with the evidence of increased cell viability. In addition, OGD/R exposure led to increase the levels of intracellular reactive oxygen species (ROS), which were significantly suppressed by tanshinone IIA treatment. Furthermore, tanshinone IIA treatment inhibited elevations in MMP and autophagy following exposure to OGD/R. Additionally, OGD/R promoted cell death with concomitant inhibiting phosphatidylinositol-3-kinase (PI3K)/protein kinase B (Akt)/ mammalian target of Rapamycin (mTOR) pathway, which was reversed by tanshinone IIA. CONCLUSION: These results suggest that the tanshinone IIA protects against OGD/R-mediated cell death in HT-22 cells, in part, due to activating PI3K/Akt/mTOR pathway.